2015
DOI: 10.1021/jacs.5b10281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanoparticulate Alloys of the Composition Cu2Zn1–xFexSnS4: Structural, Optical, and Magnetic Properties

Abstract: Nanoparticles of the semiconductor Cu2Zn(1-x)Fe(x)SnS4 with different mole fractions of iron (x(Fe)) were synthesized by the decomposition of molecular precursors in oleylamine. The composition, structure, optical, and magnetic properties of the nanoparticles are reported. The parent (Cu2ZnSnS4) zinc material is usually reported as kesteritic and the corresponding iron phase as stannitic; with different site occupancies and tetragonalities. In the small ca. 8-10 nm particles prepared, the smooth variation in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Unlike CZTS, CFTS is more stable in stannite crystal structure (ST) with an I-42m space group which shows less cationic disorder from the kesterite structure [155]. CFTS thin films have been fabricated by various methods, such as solvothermal [142], hot injection method [141], molecular method [156], spray pyrolysis [157], and mostly focused on its magnetic properties. Even though CFTS exhibit a band gap between 1-1.5 eV and high absorption coefficient (10 4 cm −1 ) in the visible spectrum range [158], there are not many reported CFTS photovoltaic devices in literature.…”
Section: Iron (Fe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike CZTS, CFTS is more stable in stannite crystal structure (ST) with an I-42m space group which shows less cationic disorder from the kesterite structure [155]. CFTS thin films have been fabricated by various methods, such as solvothermal [142], hot injection method [141], molecular method [156], spray pyrolysis [157], and mostly focused on its magnetic properties. Even though CFTS exhibit a band gap between 1-1.5 eV and high absorption coefficient (10 4 cm −1 ) in the visible spectrum range [158], there are not many reported CFTS photovoltaic devices in literature.…”
Section: Iron (Fe)mentioning
confidence: 99%
“…As for the Fe alloying in CZTS, both of Fe 2+ (0.66 Å) and Zn 2+ (0.64 Å) have similar ionic radii, which enables a solid solubility in the Cu 2 Zn x Fe 1−x SnS 4 (CZFTS) [18]. There are few studies about CZFTS thin film properties which shows transformation from kesterite to stannite and increase in band gap (ranging from 1.35 eV to 1.7 eV) as the amount of Fe increases [156,[164][165][166]. However, a combinatorial study using spray coating showed a strong detrimental effect on quasi-Fermi level splitting (QLFS) in Cu 2 Zn x Fe 1−x Sn(S,Se) 4 even at low concentrations of Fe [167].…”
Section: Iron (Fe)mentioning
confidence: 99%
“…Similarly, many other quaternary chalcogenides such as CCTS, CFTS, CMTS, CNTS and hybrids of quaternary chalcogenides with magnetic metals such as CZTS‐NiPt, CZTS‐CoPt etc. have been explored for emerging applications in magneto‐electrical devices ,,,…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…The scaled‐up synthesis procedures and versatile techniques have been established to further reduce the cost function for its effective commercial PV realization ,,. Interestingly, huge range of Cu‐based quaternary chalcogenide Cu 2 M I M II X 4 (where, M I =Zn, Ni, Co, Fe, Mn, Cd and Hg; M II =Si, Sn and Ge and X=S and/or Se) materials have been emerged in the recent time claiming vivid application of these material in diverse fields ,,,. This review presents the key features and recent developments in the direction of synthesis and multifunctional applications of these Cu‐based quaternary chalcogenides.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a method for controlling the phase of the obtained CZTS would be a major step toward commercializing CZTS. We have previously reported the synthesis of CZTS and Cu 2 Zn 1-x Fe x SnS 4 nanoparticles and thin films from the decomposition of dithiocarbamate single-source precursors (SSPs) [41][42][43].…”
Section: Introductionmentioning
confidence: 99%